The impact of national vaccination policy changes on influenza incidence in the Netherlands. Issue 2 (2nd February 2016) - McDonald, Scott A.; van Asten, Liselotte; van der Hoek, Wim; Donker, Gé A.; Wallinga, Jacco
Abstract : Background: We assessed the impact of two major modifications of the Dutch National Influenza Prevention Programme – the introduction in 1997 of free‐of‐charge vaccination to persons aged ≥65 years and to high‐risk groups (previously only advised, and not free of charge), and the lowering of the eligible age to 60 years in 2008 – on the estimated incidence of influenza infection leading to influenza‐like illness (ILI). Methods: Additive negative‐binomial segmented regression models were fitted to ILI data from GP sentinel surveillance in two‐eight‐season intervals (1993/4 to 2000/1, 2004/5 to 2011/12, comparing pre‐ and post‐policy‐change periods within each interval), with laboratory virological reporting of samples positive for influenza or other ILI‐causing pathogens as covariates. Results: For the 2008 policy change, there was a significant step decrease in influenza contribution considering all ages (=−111 per 100 positives; 95% CI: −162, −65·0), <60 years and 60–64 years age groups ( B = −92·1 per 100; 95% CI: −134, −55·5; B = −5·2; 95% CI: −10·3, −1·2, respectively). There was no evidence for a decrease associated with the 1997 policy change targeting the ≥65 years age group. Conclusions: In the Netherlands, a 56% reduction in influenza contribution was associated with the 2008 policy targeting 60–64 year‐olds, but there was no effect of the earlier policy targeting ≥65‐year‐olds, for whom vaccination coverage was already rising before the policy change.